Electronic Bone Growth Stimulators for Augmentation of Osteogenesis in In Vitro and In Vivo Models: A Narrative Review of Electrical Stimulation Mechanisms and Device Specifications - Nicksic, Peter J.; Donnelly, D’Andrea T.; Hesse, Madison; Bedi, Simran; Verma, Nishant; Seitz, Allison J.; Shoffstall, Andrew J.; Ludwig, Kip A.; Dingle, Aaron M.; Poore, Samuel O. (Frontiers in Bioengineering and Biotechnology, 2022)
Since the piezoelectric quality of bone was discovered in 1957, scientists have applied exogenous electrical stimulation for the purpose of healing. Despite the efforts made over the past sixty years, electronic bone growth stimulators are not in common clinical use. Reasons for this include high cost and lack of faith in the efficacy of bone growth stimulators on behalf of clinicians. The purpose of this narrative review is to examine the preclinical body of literature supporting electrical stimulation and its effect on bone properties and elucidate gaps in clinical translation with an emphasis on device specifications and mechanisms of action. When examining these studies, trends become apparent. In vitro and small animal studies are successful in inducing osteogenesis with all electrical stimulation modalities: direct current, pulsed electromagnetic field, and capacitive coupling. However, large animal studies are largely unsuccessful with the non-invasive modalities. This may be due to issues of scale and thickness of tissue planes with varying levels of resistivity, not present in small animal models. Additionally, it is difficult to draw conclusions from studies due to the varying units of stimulation strength and stimulation protocols and incomplete device specification reporting. To better understand the disconnect between the large and small animal model, the authors recommend increasing scientific rigor for these studies and reporting a novel minimum set of parameters depending on the stimulation modality.